Semiderivations with Power Values on Lie Ideals in Prime Rings - Huang, Shuliang (Ukrains’kyi Matematychnyi Zhurnal, 2013)
Let R be a prime ring, let L a noncentral Lie ideal, and let f be a nonzero semiderivation associated with an automorphism σ such that f(u) n = 0 for all u ∈ L; where n is a fixed positive integer. If either Char R > n + 1 or Char R = 0; then R satisfies s 4; the standard identity in four variables.